Dietary Succinate Impacts the Nutritional Metabolism, Protein Succinylation and Gut Microbiota of Zebrafish - Ding, Qianwen; Lu, Chenyao; Hao, Qiang; Zhang, Qingshuang; Yang, Yalin; Olsen, Rolf Erik; Ringo, Einar; Ran, Chao; Zhang, Zhen; Zhou, Zhigang (Frontiers in Nutrition, 2022)
Succinate is widely used in food and feed industry as an acidulant, flavoring additive, and antimicrobial agent. This study investigated the effects of dietary succinate on growth, energy budget, nutritional metabolism, protein succinylation and gut microbiota composition of zebrafish. Zebrafish were fed with a control-check (0% succinate) or four succinate-supplemented diets (0.05%, 0.10%, 0.15% and 2.0%) for 4 wks. Results showed that dietary succinate at the 0.15% additive amount (S0.15) can optimally promote weight gain and feed intake. Whole-body protein, fat and energy deposition increased in the S0.15 group. Fasting plasma glucose level decreased in fish fed S0.15 diet, along with improved glucose tolerance. Lipid synthesis of the intestine, liver and muscle increased with S0.15 feeding. Diet with 0.15% succinate inhibited intestinal gluconeogenesis but promoted hepatic gluconeogenesis. Glycogen synthesis increased in the liver and muscle of of S0.15-fed fish. Glycolysis was increased in the muscle of S0.15-fed fish. Besides, 0.15% succinate-supplemented diet inhibited protein degradation of the intestine, liver and muscle. Interestingly, different protein succinylation patterns in the intestine and liver were observed in fish fed S0.15 diet. Intestinal proteins with increased succinylation levels were enriched in tricarboxylic acid (TCA) cycle while proteins with decreased succinylation levels were enriched in pathways related to fatty acid and amino acid degradation. Hepatic proteins with increased succinylation levels were enriched in oxidative phosphorylation while proteins with decreased succinylation were enriched in the processes of protein processing and transport in endoplasmic reticulum. Finally, fish fed S0.15 diet had a higher abundance of Proteobacteria, but lower abundance of Fusobacteria and Cetobacterium. In conclusion, dietary succinate could promote growth, feed intake, drive lipid anabolism, improve glucose homeostasis and spare protein. The effects of succinate on nutritional metabolism are associated with the alterations of metabolic intermediates levels, transcriptional regulation and protein succinylation levels. However, hepatic fat accumulation and gut microbiota dysbiosis induced by dietary succinate suggest potential risks of succinate application as a feed additive for fish. This study would be beneficial for understanding the application of succinate as an aquatic feed additive.